FMPNet: a fuzzy-embedded multi-scale prototype network for sea-land segmentation of remote sensing images - Guangyi Wei; Jindong Xu; Qianpeng Chong; Jianjun Huang (European Journal of Remote Sensing)
Sea-Land Segmentation (SLS) of remote sensing images is a meaningful task in the remote sensing and computer vision community. Some tricky situations, such as intraclass heterogeneity due to imaging constraints, inherent interclass similarity of sea-land regions and uncertain sea-land boundaries, still are and continues to be the significant challenges in SLS. In this paper, a fuzzy-embedded multi-scale prototype network, named FMPNet, is proposed to target the above challenges of SLS task. We design a dual-branch joint attention feature extraction module (DAFM) for effective feature extraction. Memory bank (MB) is designed to collect multi-scale prototypes, aiming to obtain discriminative feature representations and guide feature selection. In addition, fuzzy connection (FC) unit is embedded in the network structure to mitigate the uncertain sea-land boundaries through 2D Gaussian fuzzy method. Extensive experimental results on a publicly SLS dataset and real region images captured by the Gaofen-1 satellite demonstrate the superior performance of the proposed FMPNet over the other state-of-the-art methods.